Anti-arthritic activity of aqueous-methanolic extract and various fractions of Berberis orthobotrys Bien ex Aitch - Alamgeer; Ambreen Malik Uttra; Umme Habiba Hasan (BMC, 2017)
Abstract Background The roots and stem bark of Berberis orthobotrys (Berberidaceae) have long been used traditionally to treat joint pain. Though, it has not been pharmacologically assessed for rheumatoid arthritis. The current study explores anti-arthritic activity and phytochemical analysis of aqueous-methanolic extract (30:70) and fractions (ethyl acetate, n-butanol, and aqueous) of Berberis orthobotrys roots. Methods Anti-arthritic potential was evaluated in vitro using protein denaturation (bovine serum albumin and egg albumin) and membrane stabilization methods at 12.5-800 μg/ml concentration and in vivo via turpentine oil, formaldehyde and Complete Freund Adjuvant (CFA) models at 50, 100 and 150 mg/kg doses. Also, in vitro antioxidant ability was appraised by reducing power assay. Moreover, total flavonoid content, Fourier transform infrared spectroscopy and High performance liquid chromatography of n-butanol fraction were performed. Results The results revealed concentration dependent inhibition of albumin denaturation and notable RBC membrane stabilization, with maximum results obtained at 800 μg/ml. Similarly, plant exhibited dose dependent anti-arthritic effect in turpentine oil and formaldehyde models, with maximum activity observed at 150 mg/kg. The results of CFA model depicted better protection against arthritic lesions and body weight alterations. Also, B.orthobotrys remarkably ameliorated altered hematological parameters, rheumatoid factor and positively modified radiographic and histopathological changes. Additionally, plant exhibited remarkable anti-oxidant activity. Moreover, phytochemical analysis revealed polyphenols and flavonoids. Conclusion Taken together, these results support traditional use of B.orthobotrys as potent anti-arthritic agent that may be proposed for rheumatoid arthritis treatment.